Shielding efficiency of wide-band pulses of electromagnetic radiation by shields based on the needle-punching material - V. I. Mordachev; D. A. Tsyanenka; H. D.A. Abdulhadi; H. A. Pukhir; A. M. Prudnik (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2020)
To protect electronic systems from the wide-band pulses of electromagnetic radiation, it is proposed to use the shields designed based on needle-punched and felt materials, including those with impregnating liquids. The shielding characteristics of the obtained shields were measured using a test complex of pulsed electromagnetic fields operating on the principle of reproducing ultrashort electromagnetic pulses of vertical (horizontal) polarization with the amplitude at the beginning of the working area of at least 5 and 50 kV/m. The test complex included voltage pulse generators, high-voltage coaxial cables, an antenna feeder, a digital field indicator, a cable and a remote control button. The effective frequency band of the pulse was from 130 MHz to 2.31 GHz. The pulse power at the beginning of the work was 5.34 MW. In each test, 5 packs of pulses were emitted and pulse amplitudes were measured. Each burst of pulses had a duration of 1 s. The pulse frequency in the packet was 1 kHz. The shielding efficiency averaged over the effective frequency band was calculated and the error was determined. The values of electromagnetic pulse shielding efficiency were obtained, which equaled 9.4.15.5 dB for a needle-punched material with a carbon additive, and 9.7...12.4 dB for felt fabric with a layer of polymer metallized film, which allows using them to design the shields to protect electronic systems from the destructive effects of electromagnetic weapons.